2017
DOI: 10.1292/jvms.17-0258
|View full text |Cite
|
Sign up to set email alerts
|

Porcine alveolar macrophage polarization is involved in inhibition of porcine reproductive and respiratory syndrome virus (PRRSV) replication

Abstract: Macrophage polarization is a process by which macrophages acquire a distinct phenotypic and functional profile in response to microenvironmental signals. The classically and alternatively activated (M1 and M2, respectively) macrophage phenotypes are defined by the specific molecular characteristics induced in response to prototypic pro- and anti-inflammatory cues. In this study, we used LPS/IFN-γ and IL-4 to stimulate porcine alveolar macrophages (PAMs) in vitro and investigated the expression changes of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…On the contrary, macrophages are polarized to M2 phenotype following IL-4, IL-10, or IL-13 stimulation, which triggers anti-inflammatory response (Gordon, 2003). Previous studies have shown that PAMs polarized toward M1 phenotype significantly inhibit PRRSV replication (Wang et al, 2017). In our work, LPS-treated PAMs appeared enhanced expression of proinflammatory cytokines, including IL-1β, IL-6, IL-8, and TNF-α, which are prototypical M1 macrophage markers (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, macrophages are polarized to M2 phenotype following IL-4, IL-10, or IL-13 stimulation, which triggers anti-inflammatory response (Gordon, 2003). Previous studies have shown that PAMs polarized toward M1 phenotype significantly inhibit PRRSV replication (Wang et al, 2017). In our work, LPS-treated PAMs appeared enhanced expression of proinflammatory cytokines, including IL-1β, IL-6, IL-8, and TNF-α, which are prototypical M1 macrophage markers (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4-MD2-LPS complex initiates signal transduction of IRF3 and NF-κB and consequently leads to secretion of type I interferon and inflammatory cytokines (Kawai and Akira, 2010). Moreover, LPS-stimulated PAMs polarizes toward M1 PAMs, which significantly inhibits PRRSV replication, but it remains an unclear mechanism (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, DEX inhibited the inflammation induced by HP-PRRSV, although the levels of proinflammatory cytokines in the peripheral blood were significantly decreased and long-lasting high fever and lung lesions were also observed in these HuN4-infected piglets. Despite the solvent of RU486 contained 50% ethanol (30 mg/ml), the dose used for each piglet was no more than 0.1 g/kg b.w., which has been demonstrated to have neither significant effect on the plasma cortisol levels nor anti-viral cell-mediate immune response, as well as no perceptible depression of the central nervous system [22,25]. Thus, we believe that DEX induces immunosuppression during HP-PRRSV infection, allowing enhanced viral replication and leading to high mortality.…”
Section: Discussionmentioning
confidence: 83%
“…The HP-PRRSV HuN4 strain (GenBank accession no. EF635006) was used in this study as a viral inoculum after three passages through porcine alveolar macrophages (PAMs, which were isolated using a lung lavage technique from 4 to 6-week-old specific-pathogen-free piglets that were free of PRRSV, PCV 2 , CSFV, PPV, PRV, swine influenza virus, and Mycoplasma hyopneumoniae infections as previously described [22]) with a titer of 10 5.0 TCID 50 /mL [23].…”
Section: Virusmentioning
confidence: 99%
“…There is limited in vivo research reported on PPAR pathway and PRRSV infection. However, one in vitro cell culture assay revealed that increased expression of PPAR-γ may be highly involved in the macrophage polarization during PRRSV replication and infection [44]. In addition, two important fatty acid binding proteins (FABPs 4 and 5) are associated with the PPAR pathway and its specific regulatory functions.…”
Section: Host Gene Response To Prrsv Infectionmentioning
confidence: 99%